2019
DOI: 10.3390/environments6040045
|View full text |Cite
|
Sign up to set email alerts
|

The Optimum Window-to-Wall Ratio in Office Buildings for Hot‒Humid, Hot‒Dry, and Cold Climates in Iran

Abstract: About half of the energy loss in buildings is wasted through windows. Determining the optimum window-to-wall ratio (WWR) for different building facades would reduce such energy losses. The optimum WWR is the window area that minimizes the total annual energy of cooling, heating, and lighting. The purpose of this study is to investigate the optimum WWR of different facades of an office building. For this purpose, a sample building is simulated by means of DesignBuilder software in order to investigate the annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 18 publications
0
19
1
2
Order By: Relevance
“…In studies investigating WWR for colder climates, the minimum energy consumption in samples was for those with a window area of 30–45%. 36 The optimal solution in the current study has suggested a reduction of the WWR from 59.5% to 33% in the western facades and a corresponding reduction from 23.5% to 17.2% in eastern façades. This is consistent with the earlier studies that recommend reduction in WWR to prevent thermal losses along with an optimum amount of day lighting.…”
Section: Discussionmentioning
confidence: 63%
“…In studies investigating WWR for colder climates, the minimum energy consumption in samples was for those with a window area of 30–45%. 36 The optimal solution in the current study has suggested a reduction of the WWR from 59.5% to 33% in the western facades and a corresponding reduction from 23.5% to 17.2% in eastern façades. This is consistent with the earlier studies that recommend reduction in WWR to prevent thermal losses along with an optimum amount of day lighting.…”
Section: Discussionmentioning
confidence: 63%
“…Yang et al [88] showed that the total energy consumption would increase when the WWR is increased, as half of the energy in a building is lost through the window [89]. Thus, it is important to determine the optimal WWR for different building facades to reduce such loss [90].…”
Section: Discussionmentioning
confidence: 99%
“…Design Builder is exclusive software designed to model and to evaluate the environmental design and performance of buildings. This program uses climate data provided by the EnergyPlus simulation engine to calculate the energy consumption of buildings in terms of cooling, heating, and lighting loads (Shaeri, et al, 2019). It has been used consistently in many studies in this field.…”
Section: Methodsmentioning
confidence: 99%